Mutualism between degraders and nondegraders stabilizes the function of a natural biopolymer-degrading community - Liang Liu; Changfu Tian; Miaoxiao Wang; Ying Luo; Yaru Huang; Tingting Jiang; Hongwen Zhao; Qijun Yu; Entao Wang; Jinshui Yang; Hongli Yuan (Proceedings of the National Academy of Sciences, 2025)
Natural biopolymer-degrading microbial communities drive carbon biogeochemical cycling. Within these communities, polymer degraders facilitate the growth of nondegraders by breaking down polymers through extracellular enzymes. However, the contributions of nondegraders to community dynamics, as well as the mechanisms that limit their access to degradation products, remain poorly understood. Here, we investigate EMSD5, a lignocellulose-degrading microbial community that efficiently converts corncob into isopropanol. We demonstrate that nondegraders, such as Escherichia coli , enable the growth of degraders (e.g., Lachnoclostridium sp. and Clostridium beijerinckii ) by creating anaerobic conditions and supplying biotin. Within such expanded niches, lignocellulose degradation proceeds sequentially, and the availability of breakdown products to E . coli is constrained by two interlinked processes. Specifically, Lachnoclostridium sp. produces oligosaccharides that are largely inaccessible to E . coli . A subset of these oligosaccharides is utilized by C . beijerinckii to produce monosaccharides that support E . coli growth, while glycosidase secretion by C . beijerinckii is reduced under coculture conditions. Building on these findings, we designed a synthetic consortium by coculturing C. beijerinckii with an engineered E . coli strain that expresses xylanase genes from an unculturable Lachnoclostridium . This consortium achieved isopropanol production from hemicellulose without requiring anaerobic conditions. Our findings reveal the niche-expanding role of nondegraders and the processes that constrain their access to degradation products, offering insights into maintaining stable cooperation in biopolymer-degrading communities and designing efficient consortia for biopolymer conversion.